Effects of enriched biochar and Bacillus subtilis on growth, physio-biochemical properties and fusarium wilt incidence of banana under water stress - Mohd Din, Siti Norliza (2018)
Banana (Musa acuminata cv. Berangan) is one of the most popular fruit and has great potential for commercial development since the current demand had increased drastically. However, in Malaysia, poor soil fertility, limited water availability and disease attack are among common problems in banana industry. In order to find a solution of the problems, a field study was conducted to determine the optimum enriched biochar rate for improvement of soil physicochemical properties, growth and physiological status of banana. In addition to field study, a glasshouse study was conducted to determine the effect of Bacillus subtilis inoculation in enriched biochar media and water stress on growth, physiological status and suppression of Fusarium wilt. Four different rates of enriched biochar (0, 1.5, 3.0 and 4.5 t ha⁻¹ ) were applied once by mixing with Bungor Series soil and put into a polybag with the size of 40 cm × 40 cm. One month old banana plantlets were used. The treatments were carried out for 3 months and arranged in a randomized complete block design with 4 replications. Meanwhile, in the second study, the media were prepared based on optimum rate of enriched biochar from the first study. The treatments consisted of two factors (water stress and Bacillus subtilis) arranged by split plot in randomized complete block design with three replications. The media were enriched with 0, 20, 40 and 60 mL Bacillus subtilis at the concentration 10⁸ CFU mL⁻¹ applied by soil drenching as pre-inoculation treatments and plantlets were subjected to 100% well- watered (WW), 75% medium-stressed (MS) and 50% severe-stressed (SS) treatments based on field capacity (FC) level. The plantlets inoculated with Fusarium oxysporum race 4 (FOC) one week after Bacillus subtilis treatments were applied and the plant were destructively sampled at 45 and 90 days after transplanting (DAT). The results found that soil microbial population, soil physicochemical properties (pH, CEC, total C, N, K, Ca and Mg), growth characteristics (plant height, pseudo- stem diameter, total leaf number and total leaf area), mineral content in leaf tissue (N, P, K, Ca and Mg) and photosynthesis rate increased with the increasing rate of enriched biochar and 4.5 t ha⁻¹ was selected as the best treatment. SS treatment significantly reduced growth parameters and physiological status (photosynthesis, stomatal conductance, transpiration and relative water content) and increased accumulation of proline and malondialdehyde content in plant tissue. Chlorophyll content showed increased by higher rates of Bacillus subtilis at both 45 and 90 DAT of destructive period. High concentrations of Bacillus subtilis (40 and 60 mL) also were found to reduce disease severity under SS but the value increased under MS and WW condition following the time. This finding suggested that, soil amendment with enriched biochar at 4.5 t ha⁻¹ was adequate for optimum growth at nursery level (vegetative stages up to 3 months). Inoculation of the media with higher rates of Bacillus subtilis able to improved growth, physiological status and nutritional properties of the banana plants under water stress condition, reduced the deleterious effects of stress and helped plantlets to tolerate drought stress to a higher level as compared to non-inoculated plantlets and increase resistance to Fusarium wilt.